Development of a Highly Reliable PbS QDs-Based SWIR Photodetector Based on Metal Oxide Electron/Hole Extraction Layer Formation Conditions - JinBeom Kwon; Yuntae Ha; Suji Choi; Donggeon Jung (Nanomaterials)
Recently, with the development of automation technology in various fields, much research has been conducted on infrared photodetectors, which are the core technology of LiDAR sensors. However, most infrared photodetectors are expensive because they use compound semiconductors based on epitaxial processes, and they have low safety because they use the near-infrared (NIR) region that can damage the retina. Therefore, they are difficult to apply to automation technologies such as automobiles and factories where humans can be constantly exposed. In contrast, short-wavelength infrared photodetectors based on PbS QDs are actively being developed because they can absorb infrared rays in the eye-safe region by controlling the particle size of QDs and can be easily and inexpensively manufactured through a solution process. However, PbS QDs-based SWIR photodetectors have low chemical stability due to the electron/hole extraction layer processed by the solution process, making it difficult to manufacture them in the form of patterning and arrays. In this study, bulk NiO and ZnO were deposited by sputtering to achieve uniformity and patterning of thin films, and the performance of PbS QDs-based photodetectors was improved by optimizing the thickness and annealing conditions of the thin films. The fabricated photodetector achieved a high response characteristic of 114.3% through optimized band gap and improved transmittance characteristics.